2006
DOI: 10.1093/jxb/erl083
|View full text |Cite
|
Sign up to set email alerts
|

The lack of mitochondrial complex I in a CMSII mutant of Nicotiana sylvestris increases photorespiration through an increased internal resistance to CO2 diffusion

Abstract: The cytoplasmic male sterile II (CMSII) mutant lacking complex I of the mitochondrial electron transport chain has a lower photosynthetic activity but exhibits higher rates of excess electron transport than the wild type (WT) when grown at high light intensity. In order to examine the cause of the lower photosynthetic activity and to determine whether excess electrons are consumed by photorespiration, light, and intercellular CO(2), molar fraction (c(i)) response curves of carbon assimilation were measured at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…This effect may be partially explained by higher rates of photorespiration after stomatal closure. Lastly, Priault et al (2006) showed a link between photorespiration and internal conductance in a mutant lacking complex I of the mitochondrial electron transport chain. Our results (Fig.…”
Section: Photorespiratory Fluxes Need To Be Considered When Calculatimentioning
confidence: 98%
“…This effect may be partially explained by higher rates of photorespiration after stomatal closure. Lastly, Priault et al (2006) showed a link between photorespiration and internal conductance in a mutant lacking complex I of the mitochondrial electron transport chain. Our results (Fig.…”
Section: Photorespiratory Fluxes Need To Be Considered When Calculatimentioning
confidence: 98%
“…This mutant carries a mitochondrial deletion in the nad7 gene encoding a 40-kD subunit of Complex I (Pla et al, 1995). The mutant plants develop slowly, exhibit conditional male sterility, and have no detectable Complex I, increased amounts and activity of AOX, and multiple perturbations to primary metabolism (Gutierres et al, 1997(Gutierres et al, , 1999Lelandais et al, 1998;Sabar et al, 2000;Dutilleul et al, 2003aDutilleul et al, , 2003bDutilleul et al, , 2005Pineau et al, 2005;Priault et al, 2006aPriault et al, , 2006bVidal et al, 2007). A second Complex I mutant has been described from maize (Karpova and Newton, 1999).…”
Section: Plant Complex I Mutantsmentioning
confidence: 99%
“…The properties of the CMS II mutant of Nicotiana sylvestris have been studied in some detail (Noctor et al 2004;Dutilleul et al 2005;Priault et al 2006Priault et al , 2007. It lacks a functional Complex I of the mitochondrial electron transport chain, has lower photosynthetic activity, and has higher respiratory rate than WTt (Dutilleul et al 2003).…”
Section: Cms Ii/msc16mentioning
confidence: 99%